Finland’s Election: Ideology, Power, and Critique behind the Loss of Sanna Marin in The Guardian - Murdhi Fida Alfaaz; Angelica Monalisa; Agis Andriani (TLEMC (Teaching and Learning English in Multicultural Contexts), 2023)
Finland’s prime minister election result is out, impacting a huge shock in European politics. This study examines The Guardian's coverage of the Finnish Prime Minister Sanna Marin's loss in the recent election, utilizing Ruth Wodak's approach to Critical Discourse Analysis. The study aims to uncover underlying ideologies, power relations, and potential critiques in The Guardian's coverage. The article analyzes The Guardian's April 4th, 2023, publication titled "Why did Sanna Marin lose Finland's election?" and discusses the reasons behind Marin's defeat. The article frames Marin's loss as a "shock," suggesting potential flaws in the electoral system or an unfair outcome. The article discusses various factors that led to Marin's defeat, such as her approach to the economy, foreign policy, and immigration, highlighting their potential impact on voter behavior. Additionally, the article suggests that Marin's loss may indicate a shift towards more conservative values in Finnish society, highlighting a rise in anti-immigration sentiment and a focus on economic issues. The study also considers power relations in the coverage, highlighting the opposition's successful framing of Marin as an out-of-touch elite, which may have played a significant role in swaying voters. However, the study notes that this approach only examined a single source. Further research involving multiple media sources and a mixed investigative lens is necessary to understand discursive issues comprehensively. Keywords: Finland’s Election, Sanna Marin, Discourse Historical Approach, The Guardian